The flavanone homoeriodictyol increases SGLT-1-mediated glucose uptake but decreases serotonin release in differentiated Caco-2 cells - Lieder, Barbara; Hoi, Julia Katharina; Holik, Ann-Katrin; Geissler, Katrin; Hans, Joachim; Friedl, Barbara; Liszt, Kathrin; Krammer, Gerhard E.; Ley, Jakob P.; Somoza, Veronika (PLOS ONE, 2017)
Flavanoids and related polyphenols, among them hesperitin, have been shown to modulate cellular glucose transport by targeting SGLT-1 and GLUT-2 transport proteins. We aimed to investigate whether homoeriodictyol, which is structurally related to hesperitin, affects glucose uptake in differentiated Caco-2 cells as a model for the intestinal barrier. The results revealed that, in contrast to other polyphenols, the flavanon homoeriodictyol promotes glucose uptake by 29.0 ± 3.83% at a concentration of 100 μM. The glucose uptake stimulating effect was sensitive to phloridzin, but not to phloretin, indicating an involvement of the sodium-coupled glucose transporter SGLT-1, but not of sodium-independent glucose transporters (GLUT). In addition, in contrast to the increased extracellular serotonin levels by stimulation with 500 mM D-(+)-glucose, treatment with 100 μM homoeriodictyol decreased serotonin release by –48.8 ± 7.57% in Caco-2 cells via a phloridzin-sensitive signaling pathway. Extracellular serotonin levels were also reduced by –57.1 ± 5.43% after application of 0.01 μM homoeriodictyol to human neural SH-SY5Y cells. In conclusion, we demonstrate that homoeriodictyol affects both the glucose metabolism and the serotonin system in Caco-2 cells via a SGLT-1-meditated pathway. Furthermore, the results presented here support the usage of Caco-2 cells as a model for peripheral serotonin release. Further investigations may address the value of homoeriodictyol in the treatment of anorexia and malnutrition through the targeting of SGLT-1.